Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/10408444.2013.877870
|View full text |Cite
|
Sign up to set email alerts
|

Diuron-induced rat urinary bladder carcinogenesis: Mode of action and human relevance evaluations using the International Programme on Chemical Safety framework

Abstract: Diuron, a high volume substituted urea herbicide, induced high incidences of urinary bladder carcinomas and low incidences of kidney pelvis papillomas and carcinomas in rats exposed to high doses (2500 ppm) in a 2-year bioassay. Diuron is registered for both occupational and residential uses and is used worldwide for more than 30 different crops. The proposed rat urothelial mode of action (MOA) for this herbicide consists of metabolic activation to metabolites that are excreted and concentrated in the urine, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
9
0
5
Order By: Relevance
“…Diuron is a type of herbicide that was shown to cause carcinoma of the urinary bladder at a very high frequency in a 2-year rat carcinogenicity study (Nascimento et al, 2006), and its MoA involves chemical cytotoxicity of a metabolite (da Rocha et al, 2010(da Rocha et al, , 2014. In a subacute toxicity test, hyperplasia occurred in the urinary bladder after administration of diuron at 2500 ppm via the feed for 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diuron is a type of herbicide that was shown to cause carcinoma of the urinary bladder at a very high frequency in a 2-year rat carcinogenicity study (Nascimento et al, 2006), and its MoA involves chemical cytotoxicity of a metabolite (da Rocha et al, 2010(da Rocha et al, , 2014. In a subacute toxicity test, hyperplasia occurred in the urinary bladder after administration of diuron at 2500 ppm via the feed for 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…2-Acetylaminofluorene (2-AAF), diuron [3-(3,4dichlorophenyl)-1,1-dimethylurea], and terephthalic acid (TPA) have been reported to induce tumors in rat urinary bladder in respective long-term oral administration toxicity tests (Wilson et al, 1941;McDonald et al, 1962;Nascimento et al, 2006;OECD, 2001). However, the mode of action (MoA) differs among these bladder carcinogenic substances: the MoA has been reported to involve genotoxicity for 2-AAF, which is a representative aromatic amine (Heflich and Neft, 1994;Kirkland et al, 2005); chemical cytotoxicity by in vivo metabolites for diuron (da Rocha et al, 2010(da Rocha et al, , 2014; and physical cytotoxicity due to urinary crystals for TPA (Dai et al, 2005b;Heck and Tyl, 1985;Chin et al, 1981). A comet assay is an in vivo test that can conveniently evaluate whether carcinogenicity of the urinary bladder is genotoxic or non-genotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…plants and algae). The suggested carcinogenic MOA in rats is ''metabolite-induced urothelial cytotoxicity with necrosis and cell exfoliation, consequent regenerative hyperplasia and eventually tumors'' (for a recent review, see Da Rocha et al, 2014). Although some hypotheses have been proposed to explain how diuron may induce cancer-related changes in rats and rodent cells, human cells have never been studied from this point of view and responses can be different in human cells.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…Furthermore, diuron has triggered urinary bladder mucosal necrosis in rats (Da Rocha et al, 2010;Cardoso et al, 2013). Diuron is metabolized and excreted into urine (for a recent review, see Da Rocha et al, 2014). It has been demonstrated that the cytotoxicity or hyperplastic urothelial lesions caused by diuron are not due to its precipitation and crystal formation in bladder (Da Rocha et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Indirect effects such as changes in urinary solids or pH have been shown not to be key events in diuron-induced carcinogenicity (Da Rocha et al, 2010). It is proposed that direct action of extended exposure to diuron and/or metabolic conversion to reactive metabolites excreted in the urine cause urothelial cytotoxicity and necrosis associated with sustained regenerative hyperplasia that eventually leads to neoplasia (Cohen, 1998;Da Rocha et al, 2010;Da Rocha et al, 2014).…”
Section: Introductionmentioning
confidence: 97%